Development of Anti-Theft Monitoring System in IoT Environment - Ahmad Poad, Farhana; Jusoh, Jusrorizal Fadly; A Ghani, Muhammad Iqmal (Evolution of Information, Communication and Computing System, 2022)
RFID is a technique of transmitting and receiving data wirelessly through electromagnetic transmission between two mobile devices, called an interrogator or an RFID reader and a transponder or an RFID tag. A standard RFID system consists of three major components: tags, reader, and middleware software acting as an interface between user and RFID system. Generally, RFID technology uses radio waves to transmit data from the reader to the tag, in return, reader will receives the modulated returned echoes from the tag via the reader. The tag modulates the electromagnetic waves and send the data back to the reader. RFID tags are classified into two broad categories: passive and active. Passive tag, operating without a battery, reflect the RF signal transmitted to them from reader and add information by modulating the reflected signal. In contrast to active tag, it contains a radio transceiver powered by an embedded battery. Due to the onboard radio, active tags have a longer working range than passive tag.